Morphophysiological study of digestive system of barking deer (Muntiacus muntjak Raf.) - Adnyane, I Ketut Mudite (2011)
The morphophysiology of the gastrointestinal tract of barking deer (Muntiacus muntjak Raf.) was studied macroscopically and microscopically by scanning electron microscopic, histochemical and immunohistochemical methods. The results showed that composition of teeth was similar to other small ruminants such as goats and sheep, except for the presence of canine teeth at the upper jaw. The tongue was elongated with a rounded apex and contained four types of lingual papillae: filiform, fungiform, vallate and large conical papillae. The stomach was divided into rumen, reticulum, omasum and abomasum. The rumen was sac-like in shape. The reticulum was relatively large (12.33 ± 2.08 cm) in length, while the omasum was oval and small (5.00 ± 0.50 cm) in length. On the mucosal surface of the rumen, ruminal papillae were densely distributed in all areas of the rumen. The length of intestine was relatively short (around 8.68 m) compared to the intestine of sheep and goat or other herbivores with ratio of the body length to the intestine was 1:9. The mucosal surface of the small intestine showed the presence of mucosal fold with intestinal villi, while the large intestine had only the mucosal folds. Unlike other ruminants, abomasum of barking deer possessed no cardiac glands. The salivary, stomach and intestinal glands contained acidic and neutral mucopolysaccharides, and glycoconjugates at various intensities. Chromogranin A, serotonin, gastrin, cholecytokinin, somatostatin and glucagon hormones-producing endocrine cells were present in the stomach and intestinal mucosa. The endocrine cells in the intestines were generally spindle shaped with long cytoplasmic processes ending into the lumen (open cell type) while in the stomach and large intestine, the cells were occasionally round or spherical in shape (close cell type). An uncommon distribution pattern of endocrine cells in the gastrointestinal tract of barking deer was noted for cholecystokinin- and glucagon-immunoreactive cells. Overall, the morphology of the digestive organs revealed that barking deer is concentrate selector eaters.